(untitled) (Research, Society and Development, 2023)
Objective: to describe the epidemiological profile, rate and trend of detection of syphilis during pregnancy in the municipality of Vilhena and in the state of Rondônia, from 2010 to 2020. Methodology: This is a descriptive, cross-sectional, retrospective epidemiological study with a quantitative approach, based on secondary sources of information, aiming to analyze the detected cases of syphilis during pregnancy notified in the period from 2010 to 2020 in the municipality of Vilhena and in the state of Rondônia. Results and Discussion: From the data analyzed, the age group of pregnant women detected with syphilis aged 20 to 39 years, self-declared brown, in which they did not complete elementary school and who were diagnosed in the primary clinical phase of the infection, had higher detection rates in the study period. In general, a growing trend was also identified in cases of syphilis in pregnant women over the years, where the municipality of Vilhena presented a RPV 4332.5%, and the state of Rondônia 719.62%. Conclusion: It is necessary to invest in actions and strategies that efficiently achieve the reduction of cases of syphilis in pregnant women, such as training professionals to guarantee the quality of prenatal care, and health education in the prevention of Sexually Transmitted Infections, as well as the serious implications of syphilis infection in pregnancy.